2020
DOI: 10.21203/rs.3.rs-43507/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis Of Candidate Genes Expected To Be Essential For Melanoma Surviving

Abstract: BackgroundNew approach for treating cancer is to influence on vital genes for tumors. A number of attempts have led to discovery candidate genes that are mean to be essential for surviving of tumor cells of different types. In this work, we tried to analyze genes that were previously found to be essential for melanoma surviving. We performed transient siRNA-mediated knockdown of UNC45A, STK11IP, RHPN2 and ZNFX1 in melanoma cell line A375. After that, we checked cell viability, proliferation and migrating rate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells, 27,29 but promoted migration of osteosarcoma and melanoma cells. 30,62 This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 50,63 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores (Figure 5A-H).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells, 27,29 but promoted migration of osteosarcoma and melanoma cells. 30,62 This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 50,63 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores (Figure 5A-H).…”
Section: Discussionsupporting
confidence: 71%
“…Generally, the roles of UNC‐45A in mammalian cell migration remain controversial. Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells, 27,29 but promoted migration of osteosarcoma and melanoma cells 30,62 50,63 and may reflect complex regulatory effects of UNC‐45A‐driven myofilament assembly in motile cells.…”
Section: Discussionmentioning
confidence: 98%